THE INFLUENCE OF FLIPPED CLASSROOM LEARNING MODELS USING MIND MAPPING METHODS ON ACHIEVEMENT AND SELF-RELIANCE PHYSICS LEARNING - Ayu Nur Laily Choiroh; Hena Dian Ayu; Hestiningtyas Yuli Pratiwi (Universitas Negeri Medan, 2018)
This research aims to the influence of Flipped Classroom learning model using Mind Mapping method on student achievement and independence. The design used in this study is quasi experiment. The population of the study were students of grade XI IPA MAN Gondanglegi Malang. The technique to test the hypothesis is to use the MANOVA test. The result of the appointment shows that: 1) there is influence of student's achievement in physics learning achievement that learn with Flipped Classroom learning model using Mind Mapping method with students who study physics with conventional learning model; 2) there is influence of student physics learning independence with Flipped Classroom learning model using Mind Mapping method with students who study physics with conventional learning model, 3) there is influence of Flipped Classroom learning model using Mind Mapping method to achievement and physics learning independence. Based on the results of the research, it can be concluded that the student who learn with the flipped classroom learning model using the method of mind mapping achievement and independence learning is higher than students who learn with conventional learning model